2016
DOI: 10.1515/anre-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of Slovak midlife women with cardiovascular complications

Abstract: The aim of this study was to analyse differences in body composition of women with and without cardiovascular complications. Bioelectrical parameters were measured with bioimpedance monofrequency analyser (BIA 101) and tissue electric properties were analysed by bioelectric impedance vector analysis (BIVA). The clinical sample (with CVD) consisted of 254 women ranging in age between 39 and 65 years. The sample of women without CVD consisted of 318 women in the same age range and was created from database of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Obesity is a global issue of great concern, and it is becoming more serious as living standards rise ( 3 ). Obesity has been shown to cause a variety of diseases, including cardiovascular ( 4 ) and cerebrovascular disease ( 5 ), diabetes ( 6 ), obstructive sleep apnea syndrome ( 7 ), and metabolic disorders ( 8 ). Observational studies have shown that NSOM may be associated with obesity, most of which is concentrated in the pediatric population ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a global issue of great concern, and it is becoming more serious as living standards rise ( 3 ). Obesity has been shown to cause a variety of diseases, including cardiovascular ( 4 ) and cerebrovascular disease ( 5 ), diabetes ( 6 ), obstructive sleep apnea syndrome ( 7 ), and metabolic disorders ( 8 ). Observational studies have shown that NSOM may be associated with obesity, most of which is concentrated in the pediatric population ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%